2019
DOI: 10.1101/716498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meiosis Initiates In The Fetal Ovary Of Mice Lacking All Retinoic Acid Receptor Isotypes

Abstract: 17Gametes are generated through a specialized cell differentiation process, 18 meiosis which, in most mammals, is initiated in ovaries during fetal life. It is widely 19 admitted that all-trans retinoic acid (ATRA) is the molecular signal triggering meiosis 20 initiation in mouse female germ cells, but a genetic approach in which ATRA synthesis 21 is impaired disputes this proposal. In the present study, we investigated the 22 contribution of endogenous ATRA to meiosis by analyzing fetuses lacking all RARs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Later, RA would reach the STRA8–positive GC and then possibly amplify the transcription of Stra8 . In agreement with this model, it was recently reported that RAR are dispensable for meiosis initiation in mouse fetal ovaries [39]. Following this line, the actual regulator of the meiotic switch, which was previously termed the ‘meiotic preventing substance’, remains to be identified.…”
Section: Discussionmentioning
confidence: 68%
“…Later, RA would reach the STRA8–positive GC and then possibly amplify the transcription of Stra8 . In agreement with this model, it was recently reported that RAR are dispensable for meiosis initiation in mouse fetal ovaries [39]. Following this line, the actual regulator of the meiotic switch, which was previously termed the ‘meiotic preventing substance’, remains to be identified.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have shown that RA induces the expression of STRA8, which could further switch on the meiotic genes, such as SYCP3, and repress the early PGC program to promote meiosis initiation. RA enhances this pathway through retinoic acid receptor (RAR)-mediated transcriptional regulation; however, after ablation of RARcoding genes, the FGCs robustly expressed meiotic genes, such as STRA8, REC8, and SYCP3, showing that RARs are actually dispensable for meiosis initiation 30 . Moreover, recent studies indicate that Zglp1 is partially overlapped with Nanog in mice, which is sufficient to induce the oogenic fate and meiosis entry, whereas RA augments the ZGLP1-activated oogenic program and meiosis initiation 16,31 .…”
Section: Discussionmentioning
confidence: 99%